Lineacoelotes, a new genus of Coelotinae from China (Araneae: Amaurobiidae) - Xu, Xiang; Li, Shuqiang; Wang, Xin-Ping (Zootaxa, 2008)
A new genus of Coelotinae, Lineacoelotes gen. nov., is described. Lineacoelotes includes five species from central and western China. The females of L. bicultratus (Chen, Zhao & Wang, 1991) comb. nov. from Hubei (transferred from Coelotes), the males and females of L. funiushanensis (Hu, Wang & Wang, 1991) comb. nov. from Henan (transferred from Draconarius), the females of L. nitidus (Li & Zhang, 2002) comb. nov. from Hubei (transferred from Coelotes) are redescribed, the males of L. nitidus are described for the first time. Two new species from both males and females, L. longicephalus sp. nov. from Sichuan and L. strenuus sp. nov. from Hubei, are described. The females of this new genus have distinct, unusually long spermathecal heads, and the males have a broad, long patellar apophysis and a strongly modified conductor but lack a lateral tibial apophysis and a conductor dorsal apophysis. Comparison of male palps of Lineacoelotes gen. nov. suggests that none of the modified apophyses on the dorsal edge of the conductor is homologous to the conductor dorsal apophysis found in many other Coelotinae, but this assumption should be tested in a future phylogenetic analysis. As in other Coelotinae, spinnerets of representatives of Lineacoelotes gen. nov. have PMS with 2 cylindrical spigots on the lateral sides and 2 minor ampullate spigots on the middle, and PLS long with 1–2 cylindrical spigots on its base, and the trichobothrium has a transversely striped large hood and a smooth small hood.